PENGARUH INDUSTRI MULTI LEVEL MARKETING (MLM) TERHADAP PENINGKATAN JIWA KEWIRAUSAHAAN MAHASISWA DAN MASYARAKAT - Deasy Rabiullia Fitrah dan Murhadi (Pelita - Jurnal Penelitian Mahasiswa UNY, 2008)
This research aims to 1) analyze the influence of Multi Level Marketing Industrytoward the upgrading of the students’ entrepreneurship interest and spirit, 2) describethe steps carried out in improving the image toward Multi Level Marketing, and 3)analyze the influence of MLM industry in creating work field.This research employed descriptive-inductive analysis using 50 respondents inSleman Regency, DIY. The result of the research was processed using SPPS programfor Windows 11.00. For the accurateness of the questions the researcher used themethod of dominant variable analysis, consisting of validity and reliability test whilefor the analysis of all the factors the researcher used double-linear regression method.The result of the research reveals that MLM has a great influence in upgradingthe students’ and society’s entrepreneurship spirit. This is proven by 1) the great numberof the students and society developing MLM, 2) the image improvement toward MLM ishighly needed by improving the product quality, personal service, and development.The score of adjusted R square 0.406 or 40.60 means that the independent variablesconsisting of MLM quality variable (X1), product quality variable (X2), personaldevelopment variable (X3), carrier variable (X4), and join variable (X5) have a positiveinfluence toward the productivity of MLM (Y) while the rest 60.60 is influenced by otherfactors. T-test shows that MLM quality variable has the most dominant influence towardMLM productivity (Y). It means that variable X1 is the most dominant variable towardthe MLM productivity, 3) MLM industry gives the positive contribution in creatingwork field. This can be seen from the data showing the great number of societies whohave benefited from the existence of MLM.Key Word: Multi Level Marketing, Entrepreneurship Spirit, Students and Society